Origin, Lifestyle, Development And Against Viruses And Bacteria That Endanger Our Life Struggle (Eurasian Research Bulletin, 2023)
This article describes the origin, way of life, development of viruses and bacteria that threaten our daily life, the application of a new approach to their study, and modern measures to combat them